2015
DOI: 10.2298/abs141212063y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of culturable endophytic bacteria from Moso bamboo (Phyllostachys edulis) and 16S rDNA diversity analysis

Abstract: We analyzed culturable endophytic bacteria from Moso bamboo (Phyllostachys edulis) using traditional bacterial isolation and culture methods and then studied the colony characteristics and diversity with a 16S rDNA sequence analysis. We isolated 82 endophytic bacteria strains belonging to 47 species in 26 genera from the root, rhizome, stem and leaves of Moso bamboo species from populations on Wuyi Mountain, and in the Jiangle and Changting regions. There were significant differences in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…M. oxydans represented the major number of endophytic isolates in leaves of Chinese cabbage [54]. Staphylococcus equorum was culturable endophytic bacteria from Moso bamboo (Phyllostachys edulis) [55]. In our study, the number of bacteria in the stem ends increased exponentially in control group and the number in vase solutions peaked on day 2 (about 10 6 cfu/ml).…”
Section: Discussionsupporting
confidence: 48%
“…M. oxydans represented the major number of endophytic isolates in leaves of Chinese cabbage [54]. Staphylococcus equorum was culturable endophytic bacteria from Moso bamboo (Phyllostachys edulis) [55]. In our study, the number of bacteria in the stem ends increased exponentially in control group and the number in vase solutions peaked on day 2 (about 10 6 cfu/ml).…”
Section: Discussionsupporting
confidence: 48%
“…The results of this study also identified fifteen bacterial genera with a relative abundance greater than 0.1% in the moso bamboo leaves (Table 1), which differs from the findings obtained using traditional bacterial isolation and culture methods. Yuan et al [17] isolated five genera (Pseudomonas, Micrococcus, Dermacoccus, Pantoea, and Streptomyces) from the leaves of moso bamboo stands in the Wuyi Mountain, Jiangle, and Changting regions of China. However, traditional culture-based bacterial isolation methods cannot sufficiently identify the bacteria associated with leaves, especially for the cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenz Hiltner defined the term "rhizosphere" in 1904 [15], and plant-associated microorganisms with root systems have received substantial attention in recent years [13,14,16]. Moso bamboo-associated bacteria and fungi have been isolated using culture-dependent methods [17,18] and high-throughput sequencing [19], but the latter study was primarily focused on the bamboo rhizome and pole-bacterial communities. The leaves of plants are ubiquitous global habitats that are inhabited by a diverse community of microorganisms [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Research on various plant species, including Arabidopsis thaliana (eudicot) ( Bai et al, 2015 ), rice ( Zhang et al, 2019 ; Kim and Lee, 2020 ), sorghum ( Emmett et al, 2017 ) (monocot) and Cycas panzhihuaensis (gymnosperm) ( Zheng and Gong, 2019 ) has revealed that plant compartments, environmental conditions and host phylogeny are the most predominant factors influencing plant-microbial consortia ( Bouffaud et al, 2014 ). Diverse microbes have been found in bamboo leaves, rhizomes, roots, and seeds ( Shen et al, 2014 ; Liu et al, 2017 ) based on culture-dependent and independent methods ( Yuan et al, 2015a ; Debnath et al, 2018 ), some of which were endophytic phosphorus- and potassium-solubilizing bacteria ( Yuan et al, 2015b ; Yuan et al, 2018 ). The photosynthetic rate, transpiration rate, and stomatal conductance in Phyllostachys edulis treated with these growth-promoting bacteria were all higher than in the control groups ( Yuan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%